2020
DOI: 10.1002/jper.19-0501
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiographic markers of peri‐implantitis in cigarette‐smokers and never‐smokers with type 2 diabetes mellitus at 7‐years follow‐up

Abstract: Background It is hypothesized that in the long‐term, (a) peri‐implant inflammatory variables (plaque index [PI], bleeding on probing [BOP], probing depth (PD) and crestal bone loss [CBL]) are worse in cigarette‐smokers (CS) and patients with type‐2 diabetes mellitus (T2DM) than never‐smokers (NS) without T2DM. The aim of the present 7‐year follow‐up clinical observational study was to assess the survival of dental implant in CS and NS with T2DM. Methods Study participants were divided into four groups based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Furthermore, some systemic conditions have been attributed to implant failure, such as diabetes and smoking 38 (16.1% and 25.8% in our study, respectively)—though osteoporosis was the predominant systemic condition (25.8%) in our series. Peri‐implant inflammatory conditions are increased in smokers and patients with diabetes 38–40 . However, Dreyer et al 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some systemic conditions have been attributed to implant failure, such as diabetes and smoking 38 (16.1% and 25.8% in our study, respectively)—though osteoporosis was the predominant systemic condition (25.8%) in our series. Peri‐implant inflammatory conditions are increased in smokers and patients with diabetes 38–40 . However, Dreyer et al 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Current research is focused on shedding light on the exact mechanisms and the different influence of smoking and DM on periimplant tissues. It has been observed that hyperglycemia rather than smoking induces inflammation in peri-implantitis, and at the absence of both nicotine and high glucose, smaller inflammatory responses are elicited [69]. Metanalysis data showed a 50% greater risk for peri-implantitis between diabetic and normoglycemic patients, while non-smoking diabetics exhibited almost 3.5-fold greater risk in comparison with non-smoking nondiabetic controls, indicating that hyperglycemia is an independent high-risk factor for periimplantitis.…”
Section: Effects Of Ages In Peri-implantitismentioning
confidence: 98%
“…Otros mecanismos por los que la periimplantitis se agrava en un paciente diabético mal controlado incluyen posibles alteraciones en la composición de la placa bacteriana y la acumulación de 13,23 productos finales de glicación avanzada. 24 Alqahtani et al evaluaron clínicamente las variables inflamatorias periimplantarias, indicando que estas fueron peores en fumadores y no fumadores con DM2 que no fumadores sin DM2, por lo que el estado de hiperglucemia crónica parece ser un mediador más fuerte de la inflamación periimplantaria que el tabaquismo en pacientes con DM2. para los implantes dentales.…”
Section: Factores De Riesgounclassified